Effects of 1-MCP on storage of "Queen cox" and "Bramley" apple fruit - Dauny, Paul Trevor (Cranfield University, 2007)
Better maintenance of firmness and suppression of ethylene production in 'Queen Cox' and 'Bramley' apple [Ma/us sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] fruit was achieved by prestorage applications of 1-MCP. 1-MCP concentration, exposure time and exposure temperature ranges of 0.1 to 10.0 µl r1 1-MCP, 6 to 48 h and O to 20°C, respectively, were effective on fruit subsequently stored for 2 ('Cox') and 3 ('Bramley') months in air at 3 to 4°C. However, 1-MCP had little effect on either firmness or ethylene production after 4 ('Cox') or 6 ('Bramley') months storage. Nonetheless, 1-MCP treated 'Bramley' fruit had reduced rot and superficial scald incidence compared with untreated control fruit. 1-MCP application was most effective when applied within 24 h of harvest · compared to 14 d later. Earlier-harvested 'Cox' and 'Bramley' apple fruit showed better response to 1-MCP-treatment than those harvested towards the end of the picking season. 1-MCP-treatment was shown to improve apple storage alone and in combination with controlled atmosphere (CA) storage. Furthermore, 1-MCPtreatment maintained fruit quality during shelf-life better than CA storage alone. Chlorophyll fluorescence was not demonstrated to be an effective method to determine 'Cox' and 'Bramley' apple fruit quality. There was no recorded correlation between the concentration of five antifungal compounds and 1-MCP-treatment after inoculation with Penicillium expansum or Botrytis cinerea. 1-MCP treatment for apple storage was developed for AgroFresh Inc., the holder of the 1-MCP patent. Part of this research was used for the UK efficacy trials for registration of 1-MCP as an apple storage treatment. On the 18th July 2002 the US Environmental Protection Agency (EPA) granted approval for 1-MCP to be applied to food crops. Approval was granted in the UK in time for the 2003 apple harvest, and for 2004 across Europe.